Inorganic and organic trace mineral supplementation in weanling pig diets - Thomaz, Maria C. [UNESP]; Watanabe, Pedro H.; Pascoal, Leonardo A. F.; Assis, Murilo M. [UNESP]; Ruiz, Urbano S.; Amorim, Alessandro B.; Silva, Susana Z. [UNESP]; Almeida, Vivian V.; Melo, Gabriel M. P.; Robles-Huaynate, Rizal A. (Academia Brasileira de Ciências, 2015)
A study was conducted to evaluate the s of dietary inorganic and organic trace minerals in two levels of supplementation regarding performance, diarrhea occurrence, hematological parameters, fecal mineral excretion and mineral retention in metacarpals and liver of weanling pigs. Seventy piglets weaned at 21 days of age with an average initial body weight of 6.70 ± 0.38 kg were allotted in five treatments: control diet (no added trace mineral premix); 50% ITMP (control diet with inorganic trace mineral premix supplying only 50% of trace mineral requirements); 50% OTMP (control diet with organic trace mineral premix supplying only 50% of trace mineral requirements); 100% ITMP (control diet with inorganic trace mineral premix supplying 100% of trace mineral requirements); and 100% OTMP (control diet with organic trace mineral premix supplying 100% of trace mineral requirements). Feed intake and daily weight gain were not affected by treatments, however, piglets supplemented by trace minerals presented better gain:feed ratio. No differences were observed at calcium, phosphorus, potassium, magnesium, sodium and sulfur excreted in feces per kilogram of feed intake. Treatments did not affect calcium, phosphorus, magnesium, sulfur and iron content in metacarpals. Trace mineral supplementation, regardless of level and source, improved the performance of piglets.

Um estudo foi conduzido para avaliar os efeitos de microminerais inorgânicos e orgânicos na dieta em dois níveis de suplementação, sobre desempenho, ocorrência de diarreia, parâmetros hematológicos, excreção dos minerais nas fezes e retenção dos minerais nos metacarpos e fígado de leitões desmamados. Setenta leitões desmamados aos 21 dias de idade com peso médio inicial de 6,70 ± 0,38 kg foram distribuídos em cinco tratamentos: dieta controle (sem adição de premix micromineral); 50% ITMP (dieta controle contendo premix micromineral inorgânico atendendo a somente 50% da exigência em microminerais); 50% OTMP (dieta controle contendo premix micromineral orgânico atendendo a somente 50% da exigência em microminerais); 100% ITMP (dieta controle contendo premix micromineral inorgânico atendendo a 100% da exigência em microminerais); e 100% OTMP (dieta controle contendo premix micromineral orgânico atendendo a 100% da exigência em microminerais). Consumo de ração e o ganho diário de peso não foram afetados pelos tratamentos, entretanto, os leitões suplementados com microminerais apresentaram melhor eficiência alimentar. Não foram observadas diferenças para as quantidades de cálcio, fósforo, potássio, magnésio, sódio e enxofre excretados nas fezes por quilograma de alimento consumido. Os tratamentos não afetaram os teores de cálcio, fósforo, magnésio, enxofre e ferro nos metacarpos. A suplementação com microminerais, independente dos níveis e da fonte, melhorou o desempenho dos leitões.
Keywords: Nursery phase; Performance; Weaning; Piglet; Fase de creche; Desempenho; Desmame; Leitão